IMPLEMENTATION OF SPIRITUAL TRAINING MIRACLE OF HAPPINESS FOR SUKU ANAK DALAM (SAD) IN MUARA TIKU VILLAGE, MUSI RAWAS UTARA DISTRICT - Afriantoni, Afriantoni; Asnita, Roma Nur (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The community service activity conducted by Raden Fatah State Islamic University (UIN) in Palembang aims to enhance the quality of education for the youth of the Anak Dalam (SAD) tribe in Muara Tiku Village, Karang Jaya District, Musi Rawas Utara Regency, South Sumatra. In an effort to improve the education of SAD youth, a spiritual approach that integrates local wisdom and local religious teachings is considered an effective solution. This community service program, titled "Spiritual Training Miracle of Happiness," will provide support through the Participatory Action Research (PAR) method, which encourages active collaboration between researchers and the community in designing, implementing, and evaluating the program. Through this program, it is hoped that the community can actively engage in the learning process, thereby strengthening internal capacities and promoting sustainable development. SAD youth will receive training that encompasses aspects of spirituality, local wisdom, and practical skills relevant to their daily lives. With a holistic and participatory approach, this program is expected to make a significant contribution to improving the educational quality of the Anak Dalam youth in Muara Tiku Village. The outcomes of this service are anticipated to serve as a foundation for the development of more inclusive and sustainable educational programs for marginalized communities in the region. The program is also designed to address the challenges faced by youth in accessing education, such as limited infrastructure, a shortage of teachers, and low motivation to learn. Improving the quality of youth education is a crucial key to advancing society, especially for communities living in remote and marginalized areas like Muara Tiku Village.